CELEBGRAM CREDIBILITY AND TRUST: CONSEQUENCES ON INTENTION TO BUY - Juliana Juliana; Erina Widianti; Vanessa Wijaya (Program Studi Hospitality dan Pariwisata, 2021)
ABSTRACT Social media Instagram is an opportunity for celebgram Rachel Vennya to promote Ngikan restaurant. The aim of this research was to determine the effect of celebgram credibility and trust on intention to buy. The purpose of this research is to give solution for the decreasing problem intention to buy of ngikan restaurant , through some variables such as: celebgram credibility, trust, and intention to buy. The sample used in this research were 168 respondents with a purposive sampling technique. The data analysis technique used PLS-SEM .The results confirms that the probability value on the F test is 0.000 <0.05 and the coefficient of determination (adjusted R2) is 63.5%. The conclusion of this study is that the variables of celebgram credibility and trust have a positive and significant effect on intention to buy. Keywords: Celebgram Credibility ; Trust ; intention to buy ABSTRAK Media sosial Instagram menjadi kesempatan bagi selebgram Rachel Vennya untuk mempromosikan Restoran Ngikan. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh kredibilitas dan kepercayaan selebgram terhadap niat membeli. Tujuan dari penelitian ini adalah memberikan solusi atas penurunan minat beli restoran ngikan gading serpong, melalui beberapa variabel seperti: kredibilitas selebgram, kepercayaan, dan niat membeli. Sampel yang digunakan dalam penelitian ini sebanyak 168 responden dengan teknik purposive sampling. Teknik analisis data menggunakan PLS-SEM. Hasil penelitian menunjukkan nilai probabilitas pada uji F sebesar 0,000 <0,05 dan koefisien determinasi (adjusted R2) sebesar 63,5%. Kesimpulan dari penelitian ini adalah variabel kredibilitas dan kepercayaan selebgram berpengaruh positif dan signifikan terhadap niat membeli.Kata kunci: Kredibilitas Celebgram; Kepercayaan; niat untuk membeli